Development of one-step reverse transcription PCR assay for detection of porcine epidemic diarrhoea virus in pigs - SINGH, FATEH; RAJUKUMAR, KATHERUKAMEM; SENTHILKUMAR, DHANAPAL; VENKATESH, GOVINDARAJULU; SUDHAKAR, SHASHI BHUSHAN; SINGH, VIJENDRA PAL; SANYAL, ANIKET (The Indian Journal of Animal Sciences, 2024)
The present study aimed to develop an in-house one-step reverse transcription (RT) PCR assay as a diagnostic preparedness for the detection of porcine epidemic diarrhoea virus (PEDV) in pigs. Primers and gene construct targeting the nucleoprotein gene of PEDV were designed and synthesised. In vitro transcribed (IVT) RNA synthesised from linearised plasmid DNA containing the gene of interest was used as the positive control for the development of the RT-PCR assay. The RT-PCR protocol was optimised using different concentrations of molecular reagents, the gradient of annealing temperatures and other thermal cycling conditions. Analytical sensitivity of the RT-PCR assay was determined using 10-fold serial dilutions of the IVT-RNA directly and of the RNA extracted from swine faeces spiked with the IVT- RNA. The developed RT-PCR assay had analytical sensitivity of 939 and 2682 RNA copies at 10-7 and 10-6 dilutions in IVT-RNA directly and RNA extracted from spiked faeces, respectively. The RT-PCR assay was found to be specific for PEDV, without any amplification for classical swine fever virus, swine influenza virus, porcine reproductive and respiratory syndrome virus and transmissible gastroenteritis virus. All the known negative field faecal samples (n=126) of pigs tested negative by the developed RT-PCR. The one-step RT-PCR assay developed in the present study will be highly useful in specific diagnosis of the disease in the event of its future ingression, and will also aid in monitoring of PED in Indian swine population.